Anatomy in dentistry: From the beginnings to contemporary reality. Issue 6 (9th April 2022) - Bernardi, Sara; Angelone, Anna Maria; Macchiarelli, Guido
Abstract: The history of dentistry and medicine has a deep and ancient bond with the history of anatomy. From the ancient times to the present, the study of the human body represents the basis for research and clinical therapy. The historical contribution of anatomists to the development of dental medicine also helped in its characterization as an integrated but special and independent branch of medicine. From Galen's studies on animals to the discoveries of dental hard tissues characteristics using a microscope, this paper provides a brief literature review of how anatomy broadly contributed to the development of the dental sciences and how it still allows us to direct critical and fundamental anatomical‐clinical paths for modern patient care. The history of the anatomy of teeth, description of skull bones, maxillary sinus characterization, the salivary glands, the tongue and labial musculature, and the microscopic anatomy of dental hard tissues will be examined. Historical research on the understanding of and progress in the oral field is of utmost importance in current clinical practice, thus inducing a future orientation in research. Most of the research especially that connected to the more distant historical periods has seen as main characters great personalities of morphological sciences, which contributes constituted fundamental basis for dental clinical aspects. Through a punctual and continuous historical assay, the ancient insights are reconnected to more recent knowledge and distinct research, thus permitting a detailed reconstruction of the historical‐anatomical course in the progress of knowledge regarding the oral cavity and related anatomical structures.